Printable RF Antennas for Power Harvesting in Paper Electronics: Optimisation of Printable Materials and Substrates - Pinheiro, Miguel Fernando Andrade (2019)
This work documents the optimisation and fabrication of Radio Frequency Identification (RFID) antennas on paper substrates to be adapted and used at 13.56 MHz. The optimisation of the antenna layout was made by inkjet printing and after that compared with two other printing techniques: flexography and screen printing. Commercial silver (Ag) nanoparticles (NPs) based inks were used to obtain conductive paths. The inkjet ink was characterised by Thermogravimetric Analysis and Differential Scanning Calorimetry (TGA-DSC) and Viscometer to know the effect of temperature on the ink components. Absorbance measurements were also done from 200 to 800 nm to know at which wavelength more energy is absorbed by the ink, which had a maximum peak at 320 nm. Three different types of paper were studied (Office, INCM Coated and INCM Uncoated) and morphologically characterised by TGA-DSC, Scanning Electron Microscopy with Energy Dispersive Spectroscopy for surface element detection and profilometry for surface roughness study. From the studied papers, INCM Coated paper presented an average roughness of 1015 nm and hydrophilic behaviour with a 68.8º contact angle. It also showed better resistance to the temperature when compared with Office and INCM Uncoated paper. The layout suffered different modifications over time to ease the inkjet fabrication and reduce the pad-to-pad resistance. The final design was used in the three printing techniques. Inkjet printing showed higher resolution and printing quality, although the printing process and the sintering time were slower. For inkjet, INCM Coated was the paper that better exhibited the least resistive conductive paths, reaching 106 Ω. Office and INCM Uncoated lowest resistance values reached 140 Ω for that technique. Interesting results were obtained by screen printing, in which all the selected substrates presented low values between 17 Ω and 35 Ω. With this, the objective was achieved, since RFID antennas were successfully produced, and a proof of concept was done.